Reference Service, Government Information, and COVID-19. Issue 3 (18th August 2022) - Hackstadt, Angela; Adams, Abigail D.
Abstract: The authors designed and distributed two surveys to answer the questions of whether the 2020 federal response to the COVID-19 pandemic affected academic librarians' trust in government information, and whether it affected the way they use government information professionally. The results showed a limited decrease in trust in 2020, somewhat mitigated by the administration turnover in 2021. Many librarians already discussed considerations such as bias, authority, and disinformation when recommending government information to students, and others indicated they are more likely to do so going forward. They will also use or suggest more caution with government documents than before. Reference interactions do not always allow the necessary time and space for a nuanced conversation about the limits of government information, so libraries and academic institutions should look for other ways to improve student political literacy as well.